Pengembangan Handout Model Elicitingactivities (MEAS) dengan Multi Representasi untuk Meningkatkan Kemampuan Pemodelan Matematis Peserta Didik SMA - Rizky Intan Fajarwaty; Siska Desy Fatmaryanti; Sriyono Sriyono (Radiasi : Jurnal Berkala Pendidikan Fisika, 2018)
Abstact - Research has been conducted to develop a Model-Eliciting Activities (MEAs) handout with multiple representations that are feasible and able to improve students' mathematical modeling abilities. The research design refers to ADDIE namely analysis, design, development, implementation, and evaluation. This research was conducted in SMA Negeri 2 Purworejo with research subjects in a limited trial of 10 students, and 32 students in the application phase. Product trials using a posttest-only control design. Data collection techniques using observation, questionnaires and tests. The results of data analysis namely the quality of handouts can be seen from the aspects of validation, the implementation of learning, students' responses to the handouts and completeness of learning outcomes. The results of the MEAs handout validation with multiple representations of three validators, namely two expert lecturers and physics teachers with an overall assessment score of 3.52 (very good). The percentage of the learning outcomes of the four meetings was 90.39% (very good). Students' responses to the handout obtained a percentage of 84.51% (good). The percentage of completeness of learning outcomes using handouts in the experimental class was 78.13%. Increasing or not the ability of mathematical modeling using hypothesis testing with t-test statistics obtained t-count of 4.548 where the magnitude of t table is 2,000 with a significant level of 0.05. H0 is rejected if the test criteria in the hypothesis test are t_count> t_table = 4,548> 2,000 then the use of Model-Eliciting Activities (MEAs) handouts with multiple representations can improve mathematical modeling abilities. The assessment results indicate that the developed handouts have good quality and can improve mathematical modeling abilities.